2020
DOI: 10.1002/pits.22414
|View full text |Cite
|
Sign up to set email alerts
|

The use of video‐based instruction to promote independent performance of physical activity skills in students with developmental disabilities in a school and community setting

Abstract: School psychologists are well-positioned to assist practitioners in engaging students in physical activity (PA) which can increase student access to improved well-being and associated health benefits. This may be of particular importance for adolescents with moderate to severe developmental disabilities (DD; autism and intellectual disability) who display various deficits in performing PA skills. Previous research suggests video-based instruction (VBI) effectively facilitated independence associated with PA sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The previous research exploring the Exercise Buddy app found independence increased but was limited to much fewer exercises (two or three, Bassette et al., 2018; five, Bassette, Weissmann et al., 2020; and six, Bassette et al., 2021). Furthermore, the ability of the participants to create their workouts in the Exercise Buddy app in this study and maintain independence across the phases of the study provides additional support for the use of the video‐prompting to teach this skill as was found in the previous research (Bassette, Dieringer et al., 2020; Bassette, Weissmann et al, 2020; Bassette et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The previous research exploring the Exercise Buddy app found independence increased but was limited to much fewer exercises (two or three, Bassette et al., 2018; five, Bassette, Weissmann et al., 2020; and six, Bassette et al., 2021). Furthermore, the ability of the participants to create their workouts in the Exercise Buddy app in this study and maintain independence across the phases of the study provides additional support for the use of the video‐prompting to teach this skill as was found in the previous research (Bassette, Dieringer et al., 2020; Bassette, Weissmann et al, 2020; Bassette et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…Previous research explored the use of the Exercise Buddy app's features in conjunction with other behavioral components (e.g., prompting, reinforcement, and incremental increase of criteria) and found physical activity skills increased across various settings including: school and community (Bassette, Dieringer et al., 2020), home and community (Bassette et al., 2018), and community only settings (Bassette, Weissmann et al., 2020; Bassette et al., 2021). Participants reported that they enjoyed using the app to learn physical activity skills; however, the number of physical activity skills explored in this preliminary research was limited (e.g., Bassette et al., 2018 only included two or three exercises).…”
Section: Introductionmentioning
confidence: 99%
“…Various intervention programs have been suggested for reaching this goal. Many of those programs were based on the use of staff supervision and prompts to support the participants' activity engagement with or without the involvement of exercise devices (e.g., treadmills and stationary bicycles) [14][15][16][17][18][19]. Other programs were based on the use of interactive technologies, that is, technologies monitoring the participants' activity engagement and responding to it with the delivery of positive (potentially motivating) stimulation [7,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of intervention programs have been suggested for this purpose. A number of those programs, for example, were based on the use of staff, parents, or caregivers' supervision and prompts for guiding the participants through various forms of activity, which could also involve the use of exercise devices (eg, treadmills and stationary bicycles) [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%